An Apolipoprotein CIII-Derived Peptide, Hatktak, Activates Macromolecular Activators of Phagocytosis from Platelets (MAPPs) - Sakamoto, Haruhiko; Ueno, Masaki; Bin, Wu; Nagai, Yumiko; Matsumoto, Kouichi; Yamanaka, Takao; Tanaka, Sumiko (IntechOpen, 2012)
None